Photocatalytic remediation of treated palm oil mill effluent contaminated with phenolic compounds using tio2 nanomaterial - Nawaz, R. (Desalination Publications, 2020)
The photocatalytic remediation efficiency of treated palm oil mill effluent (POME) containing phenolic compounds was investigated employing TiO2 nanomaterial. The TiO2 was produced via chemical precipitation method using TiCl4 as a precursor, water and aqueous glycerol solution as synthesis media. The structural, optical, morphological and textural properties of TiO2 were ana-lyzed by Raman spectroscopy and X-ray diffraction, diffuse reflectance UV-Visible spectroscopy, field-emission scanning electron microscopy and BrunauerâEmmetâTeller total surface area analysis. The results demonstrated that TiO2 synthesized in aqueous glycerol solution exhibited an excellent redshift of the optical response into the visible light region with a narrow bandgap of 2.96 eV which led to improved remediation efficiency of treated POME. The particle size range of TiO2 prepared with and without glycerol was 14.98â24.51 nm and 13.02â17.37 nm, respectively. The effect of TiO2 loading and H2 O2 dosage were optimized using a central composite design and their optimum levels were determined as 0.9 g/L and 1.5985 mol/L, respectively. Under the optimized conditions, 78.32 of 224.85 mg/L phenolic compounds were degraded within 180 min of visible light irradiation using the glycerol-mediated synthesized TiO2 . For comparison, the performance of TiO2 photocatalyst prepared in water achieved 67 photocatalytic degradation of phenolic compounds in treated POME. Â© 2020 Desalination Publications. All rights reserved.